2006
DOI: 10.1111/j.1471-4159.2006.03850.x
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation‐induced increase in α4 and δ subunit gene expression is associated with a greater efficacy of ethanol on steroidogenesis and GABAA receptor function

Abstract: Previously we have demonstrated that social isolation of rats reduces both the cerebrocortical and plasma concentrations of 3a-hydroxy-5a-pregnan-20-one (3a,5a-TH PROG), and potentiates the positive effects of acute ethanol administration on the concentrations of this neurosteroid. We now show that the ethanol-induced increase in 3a,5a-TH PROG is more pronounced in the brain than in the plasma of isolated rats. The ability of ethanol to inhibit isoniazid-induced convulsions is greater in isolated rats than in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 47 publications
6
55
3
Order By: Relevance
“…In contrast, a decrease in the frequency of sIPSCs has been observed following chronic mild stress in DGGCs (Holm et al, 2011), which is consistent with a decrease in the expression of the α1/α2 and γ2 subunits (Matsumoto et al, 2007). Consistent with an upregulation of the GABA A R α4, α5 and δ subunit (Serra et al, 2006; Matsumoto et al, 2007), an increase in tonic GABAergic inhibition has been measured in DGGCs following chronic stress (Serra et al, 2008; Holm et al, 2011). In the PVN, a decrease in the frequency of sIPSCs has been observed (Verkuyl et al, 2004), which can be mimicked with exogenous corticosterone (Verkuyl et al, 2005) and reversed with adrenalectomy (Verkuyl and Joels, 2003).…”
Section: Stress-induced Alterations In Gabaergic Inhibitionmentioning
confidence: 63%
See 1 more Smart Citation
“…In contrast, a decrease in the frequency of sIPSCs has been observed following chronic mild stress in DGGCs (Holm et al, 2011), which is consistent with a decrease in the expression of the α1/α2 and γ2 subunits (Matsumoto et al, 2007). Consistent with an upregulation of the GABA A R α4, α5 and δ subunit (Serra et al, 2006; Matsumoto et al, 2007), an increase in tonic GABAergic inhibition has been measured in DGGCs following chronic stress (Serra et al, 2008; Holm et al, 2011). In the PVN, a decrease in the frequency of sIPSCs has been observed (Verkuyl et al, 2004), which can be mimicked with exogenous corticosterone (Verkuyl et al, 2005) and reversed with adrenalectomy (Verkuyl and Joels, 2003).…”
Section: Stress-induced Alterations In Gabaergic Inhibitionmentioning
confidence: 63%
“…Chronic social isolation stress results in a decrease in α1 and α2 expression and an increase in α4 and α5 expression in the frontal cortex (Matsumoto et al, 2007). Similarly, an increase in α4 and δ subunit expression has been observed in the hippocampus following chronic social isolation stress (Serra et al, 2006). These changes are summarized in Table 2, highlighting the brain region-specific alterations in GABA A Rs following chronic stress.…”
Section: Stress-induced Alterations In Gabaergic Inhibitionmentioning
confidence: 77%
“…Immunoblot analysis showed that these antibodies recognized a single protein of ϳ70 kDa in a crude membrane fraction prepared from rat hippocampal neurons (Sanna et al, 2003). The specificity of this antibody preparation was also confirmed by immunocytochemistry (Sanna et al, 2003;Serra et al, 2006). The antibodies to the ␥ 2 subunit were generated in response to a synthetic peptide corresponding to residues 39 -53 of the rat protein.…”
Section: Methodsmentioning
confidence: 82%
“…Immunoblot analysis of a crude membrane fraction of the rat hippocampus with these antibodies yielded a single immunoreactive band at a position corresponding to a molecular size of ϳ54 kDa (Follesa et al, 2005). The specificity of the antibody preparation was also confirmed by immunocytochemical analysis (Follesa et al, 2005;Serra et al, 2006). The antibodies to the ␣ 4 subunit were generated in response to a peptide corresponding to the N-terminal region of the rat protein.…”
Section: Methodsmentioning
confidence: 91%
“…In fact, one recent study (Serra et al, 2006) demonstrated that low dose (25 mM) ethanol increased inhibitory current in hippocampal neurons under conditions of high α4βδ GABAR expression. This effect increased progressively over time, with peak level noted by 20 min after ethanol exposure.…”
Section: Discussionmentioning
confidence: 99%